The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.2527/2005.8371568x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of supplemental magnesium, tryptophan, vitamin C, and vitamin E on stress responses of pigs to vibration1

Abstract: Our objectives were to investigate and compare the effects of supplemental Mg, Trp, vitamin E (vit E), and vitamin C (vit C) on stress responses of pigs undergoing transport simulation. In this study, 126 pigs (25.1 +/- 4.4 kg BW) were allocated to one of the six following treatments: 1) negative control (no supplementation); 2) positive control (i.m. injection with 0.5 mg of carazolol/20 kg BW 12 h before vibration, beta-blocker); 3) Trp (additional amount of 6 g/kg of feed for 5 d, as-fed basis); 4) Mg (3 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
4
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 42 publications
2
40
4
8
Order By: Relevance
“…While these findings disagree with two studies in which supplemental Trp increased lying behaviour (Peeters et al 2004;Li et al 2006), they are consistent with other studies which have found no influence of Trp supplementation in feed on pig behaviour (Koopmans et al 2005;Peeters et al 2005;Panella-Riera et al 2009). …”
Section: Behaviourcontrasting
confidence: 56%
See 1 more Smart Citation
“…While these findings disagree with two studies in which supplemental Trp increased lying behaviour (Peeters et al 2004;Li et al 2006), they are consistent with other studies which have found no influence of Trp supplementation in feed on pig behaviour (Koopmans et al 2005;Peeters et al 2005;Panella-Riera et al 2009). …”
Section: Behaviourcontrasting
confidence: 56%
“…This result was explained by the fact that Trp and NEFA share the same carrier, i.e., albumin (Davis et al 2000). However, in other studies, Peeters et al (2004Peeters et al ( , 2005 reported that Trp supplementation had no effect on blood NEFA levels as in the present study. Nevertheless, NEFA content tended to be lower by over 20% (P 00.09) in HF pigs when compared with CONT; this may reflect a lower utilization of body reserves during fasting in these pigs and higher resistance to fasting.…”
Section: Physiological Measurescontrasting
confidence: 56%
“…Conversely, supplementation with ractopamine, which increases activity in pigs, is associated with increased oral-nasal behaviour and aggression (Poletto et al, 2010b). A limited number of studies demonstrate welfare benefits probably arising from a reduction in negative behaviours associated with supplementing pig diets with magnesium (Mg) because of what appears to be its 'calming' effect (Kuhn et al, 1981;Peeters et al, 2005 and. Thus, there is the potential for Mg supplementation to also help reduce the performance of negative behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is the potential for Mg supplementation to also help reduce the performance of negative behaviours. Peeters et al (2005) suggested that Mg supplementation improved the pigs' ability to cope with the stress of vibration by blocking the sympathetic pathways of the autonomic nervous system. Meanwhile, Kietzmann and Jablonski (1985) reported lower plasma corticosteroids, plasma catecholamines and neuromuscular stimulation in pigs supplemented with Mg.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, exposure to long--term road traffic noise in both children and adults leads to elevated night time secretion of noradrenaline and cortisol when compared to controls (Ising and Braun, 2000). Mg administration is effective in diminishing ototoxicity (Abaamrane et al, 2009;Ehrenberger and Felix, 1995) as well as in alleviating transportation stress (Tang et al, 2008;Peeters et al, 2005). Cold stress also induces a decrease in Mg levels in CSF and raises the incidence of clinical manifestations (Matsui, 2007).…”
Section: Magnesium Interaction With Stress Pathwaysmentioning
confidence: 99%